Treatment Specific Changes in Decentering Following Mindfulness-Based Cognitive Therapy Versus Antidepressant Medication or Placebo for Prevention of Depressive Relapse - Bieling, Peter J. (2012)
OBJECTIVE: To examine whether meta-cognitive psychological skills, acquired in MBCT are also present in patients receiving medication treatments for prevention of depressive relapse and whether these skills mediate MBCT's effectiveness. METHOD: This study, embedded within a randomized efficacy trial of MBCT, was the first to examine changes in mindfulness and decentering during 6-8 months of antidepressant treatment and then during an 18 month maintenance phase where patients either discontinued medication and received MBCT, continued on antidepressants, or were switched to a placebo. A total of 84 patients (mean age 44, 58% female) were randomized to one of these three prevention conditions. In addition to symptom variables, changes in mindfulness, rumination and decentering were assessed during the phases of the study. RESULTS: Pharmacological treatment of acute depression was associated with reductions in Rumination and increased Wider Experiences. During the maintenance phase, only patients receiving MBCT showed significant increases in the ability to monitor and observe thoughts and feelings as measured by the Wider Experiences (p<.01) and Decentering (p<.01) subscales of the Experiences Questionnaire and Toronto Mindfulness Scale. In addition, changes in Wider Experiences (p<.05) and Curiosity (p<.01) predicted lower HRSD scores at 6 months follow up. CONCLUSIONS: An increased capacity for decentering and curiousity may be fostered during MBCT, and underlie its effectiveness. With practice, patients can learn to counter habitual avoidance tendencies and to regulate dysphoric affect in ways that support recovery.